Aesthetic Rehabilitation of a Patient with Bruxism Using Ceramic Veneers and Overlays Combined with Four-Point Monolithic Zirconia Crowns for Occlusal Stabilization: A 4-Year Follow-Up - André Moreira; Filipe Freitas; Duarte Marques; João Caramês (Case Reports in Dentistry)
Management of severe worn dentition in patients with bruxism is challenging as a result of the loss of tooth structure and occlusal vertical dimension, temporomandibular implications, tooth hypersensitivity, and masticatory or aesthetic impairment. This case describes the 4-year follow-up clinical evaluation of a full mouth tooth-supported rehabilitation made on a 66-year-old man with bruxism and tooth wear, with aesthetic complaints and compromised masticatory function. The prosthetic treatment was planned with a digital smile design and a mock-up technique for an aesthetic and minimally invasive approach using lithium disilicate pressed and layered veneers on anterior teeth, posterior CAD/CAM lithium disilicate overlays with facial coverage, and CAD/CAM monolithic zirconia crowns with facial feldspathic ceramic on maxillary and mandibular canines and first molars in order to ensure the occlusal stability at the increased occlusal vertical dimension. After 4 years of function, no complications were registered. The choice of an appropriate material for the rehabilitation of these patients is essential to improve treatment prognosis and should be guided by mechanical and aesthetical properties. The use of four-point occlusal stabilization with CAD/CAM high strength monolithic zirconia crowns combined with ceramic veneers and overlays appears to be a reliable treatment option that enhances aesthetics and minimizes the occurrence of ceramic fractures, ensuring the treatment prognosis and predictability.